Cenomanian sequence stratigraphy and sea-level fluctuations in the Tarfaya Basin (SW Morocco) - Kuhnt, W; Holbourn, A; Gale, A; Chellai, E; Kennedy, W (2009)
We investigated the sequence architecture of two expanded Cenomanian successions along a depth transect in the Tarfaya Basin (SW Morocco) and correlated these successions to published records from northwest Europe and India. Changes in terrigenous material, carbonate and organic carbon content, carbonate microfacies and foraminiferal biofacies, as well as nondepositional and erosional surfaces were used to define depositional sequences and systems tracts. We identified two main transgressive cycles in the lower and middle-upper Cenomanian separated by a major regression at the early-middle Cenomanian transition (sequence boundary Ce 3). This regressive interval is characterized by lagoonal low- stand deposits indicating an overall sea- level fall of more than 30 m. Superimposed on the two main transgressive cycles, there are 11 third-order depositional sequences that correlate to globally recognized sea-level fluctuations and appear to be paced by long eccentricity variations (400 Ka period). Positive carbon isotope excursions in the middle Cenomanian (96.0 Ma) and latest Cenomanian (94.0 Ma) following sea- level lowstands together with planktonic foraminiferal and ammonite datums pro- vide a robust framework for stratigraphic correlation. We suggest that the onset of these excursions was triggered by eccentric- ity minima during periods of low variability in obliquity (nodes), which probably coincided with glacioeustatic lowstands. © 2009 Geological Society of America.